Exploring the Correlation Between GPR176, a Potential Target Gene of Gastric Cancer, and Immune Cell Infiltration - Gu X; Shen H; Xiang Z; Li X; Zhang Y; Zhang R; Su F; Wang Z (Dove Medical Press, 2023)
Xianhua Gu,1,* Honghong Shen,2,* Zheng Xiang,3 Xinwei Li,2 Yue Zhang,2 Rong Zhang,1 Fang Su,2 Zishu Wang2 1Department of Gynecology Oncology, First Affiliated Hospital of Bengbu Medical College, Bengbu, People's Republic of China; 2Department of Medical Oncology, First Affiliated Hospital of Bengbu Medical College, Bengbu, People's Republic of China; 3Department of Surgical Oncology, First Affiliated Hospital of Bengbu Medical College, Bengbu, People's Republic of China*These authors contributed equally to this workCorrespondence: Fang Su; Zishu Wang, Department of Medical Oncology, The First Affiliated Hospital of Bengbu Medical College, Anhui Province Key Laboratory of Translational Cancer Research, Bengbu Medical College, 287 Changhuai Road, Bengbu, Anhui, 233004, People's Republic of China, Tel +8613605523272 ; +86 18909620171, Email sufang2899@163.com; wzshahbb@163.comIntroduction: GPR176, an orphan G protein-coupled receptor (GPCR), is essential for the progression of gastrointestinal cancers. However, it is still unclear how GPR176 affects tumor immunity and patient prognosis in gastric cancer (GC).Methods: The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) were searched in this investigation to assess the expression patterns of GPR176 in GC tissues and normal gastric mucosa. The findings were further verified using immunohistochemical tests and quantitative Real-Time Polymerase Chain Reaction (qRT-PCR). The Kaplan-Meier method, univariate logistic regression, and Cox regression were then used to investigate the relationship between GPR176 and clinical traits. Additionally, the potential correlation between GPR176, immune checkpoint genes, and immune cell infiltration levels was investigated.Results: As per the research findings, GC tissues had higher levels of GPR176 than normal tissues. Additionally, individuals with high expression of GPR176 had a worse 10-year overall survival (OS), in contrast with those having a low expression of GPR176 (p < 0.001). The OS of GC can be predicted using a validated nomogram model. The expression of GPR176 demonstrated a negative correlation with CD8+ T cells. When compared to the low-expression group of GPR176, Tumor Immune Dysfunction and Exclusion (TIDE) analysis demonstrated that the high-expression group had a considerably higher risk of immune evasion. A remarkable difference (variation) was observed in the levels of GPR176 expression across both groups, ie, low and high-risk groups, as determined by the immune phenomenon scores (IPS) immunotherapy assessment.Conclusion: By examining GPR176 from various biological perspectives, it was determined that GPR176 can act as a predictive biomarker for poor patient prognosis in GC. Additionally, it was observed that GPR176 is capable of suppressing the proliferation of CD8+ T cells and facilitating immune evasion.Keywords: GPR176, gastric cancer, tumor microenvironment, immunotherapy, immune escape